2012
DOI: 10.1103/physreva.85.043403
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of ionization in direct-frequency comb spectroscopy

Abstract: Direct-frequency comb spectroscopy (DFCS) is currently the highest-resolution absolute frequency spectroscopic technique known. In general, one does DFCS by scanning the repetition rate, f rep , of a comb laser and measuring fluorescence from the excited states of the species under study. The technique has already been successfully characterized by a theoretical model that starts with the optical Bloch equations and, with a few simplifying assumptions converts them into linear coupled iterative equations. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In a recently published theoretical study of frequency comb light interacting with 87 Rb 10 Lomsadze et al computed the relative populations of the 5s, 5p, 5d, and the continuum states. It was found that the structure of the ion spectrum was essentially identical to that of the 5d, and that the ion population was substantially greater.…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published theoretical study of frequency comb light interacting with 87 Rb 10 Lomsadze et al computed the relative populations of the 5s, 5p, 5d, and the continuum states. It was found that the structure of the ion spectrum was essentially identical to that of the 5d, and that the ion population was substantially greater.…”
Section: Introductionmentioning
confidence: 99%